Dynamic Model and Robust Control of Flexible Link Robot Manipulator - Mohammad Khairudin; Zaharuddin Mohamed; Abdul Rashid Husain (Universitas Ahmad Dahlan, 2011)
The problems of a flexible link manipulator are uncertainties and parametric nonlinearities. This paper presents design and development of a robust control based on linear quadratic regulator (LQR) for a flexible link manipulator. System performances were evaluated in terms of input tracking capability of hub angular position response, end-point displacement, end-point residual and hub velocity. For the controller of the system, LQR was developed to solve flexible link robustness and input tracking capability of hub angular position. The results achieved by the proposed controller are compared with conventional PID, to substantiate and verify the advantages of the proposed scheme and its promising potential in control of a flexible link manipulator. The robust control presented faster settling time and smaller overshoot responses and tracking performances of the proposed controller compared with PID controllers.